Online Programming Group Network (OPGN) / Kok Chun Jye - Kok , Chun Jye (2005)
Online Programming Group Network is a web portal with the programming as the main focus. It is a portal which develop special to manage programming problems faced by FSKTM members. By using the system, users can access useful link to other programming sites which posses a lot of notes or tutorial, post question in forum and also chat with other user to discuss the same problems that they are facing. The main objective of the system is to provide students an avenue to communicate with other not only among students but also lecturers and tutors regarding programming problem they face. Therefore, it is hoping that this system will assist them to easily get different kind of programming problems. In this project, Unified Process has been chosen to develop the system. Besides, special development technology and tools like ASP.NET, Internet Information Server(IIS), and Microsoft Visual Studio .Net, Microsoft SQL Server 200 are need in the software development. The target users of the system are FSKTM's Lecturers, tutors and student.